English Neologisms and How to Translate Them (Texas Journal of Multidisciplinary Studies, 2022)
This paper deals with such layer of English vocabulary as neologisms. It defines the concept of neologisms, the main reasons for the emergence of new words, and indicates the sources in which they are contained, e.g. Cambridge Dictionary, Oxford English Dictionary, Macmillan Dictionary and MerriamWebster Dictionary. The paper offers the detailed classification of neologisms based on the method of their formation and describes their features giving several examples for each type, e.g. phonological neologisms, borrowings and morphological neologisms, which are formed by affixation, composition, conversion and contraction. In addition, it draws attention to the problem of translating neologisms and the authors list various techniques of translating them, e.g. transcription, transliteration, calquing, and descriptive translation, each of which being characterized and accompanied by an example taken from one of the abovesources.